2014
DOI: 10.1075/dujal.3.1.01sil
|View full text |Cite
|
Sign up to set email alerts
|

Establishing coherence in schoolbook texts

Abstract: This article focuses on the influence of connectives (because,so) and layout (continuous placement of sentences versus each sentence beginning on a new line) on the quality of students’ mental representations. By using multiple comprehension tasks, we found that cohesive text features have different effects on each facet of deeper text comprehension. On local comprehension tasks (i.e. bridging inference questions), all students performed better after reading history texts containing connectives than after read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
(122 reference statements)
0
10
0
1
Order By: Relevance
“…In addition, readers generate more inferences from discourse relations conveyed by connectives compared to implicit relations (Millis, Golding & Barker, 1995;Degand, Lefèvre & Bestgen, 1999) and they also answer questions faster (Millis & Just, 1994). Even young readers benefit from the presence of connectives (Mouchon, Fayol & Gaonac'h, 1995;Cain & Nash, 2011, van Silfhout et al, 2014. Conversely, when connectives are not correctly used to mark coherence relations, Paper published in: Second Language Research DOI: 10.1177/0267658315573349…”
Section: Importance For Text Processing and Comprehensionmentioning
confidence: 99%
“…In addition, readers generate more inferences from discourse relations conveyed by connectives compared to implicit relations (Millis, Golding & Barker, 1995;Degand, Lefèvre & Bestgen, 1999) and they also answer questions faster (Millis & Just, 1994). Even young readers benefit from the presence of connectives (Mouchon, Fayol & Gaonac'h, 1995;Cain & Nash, 2011, van Silfhout et al, 2014. Conversely, when connectives are not correctly used to mark coherence relations, Paper published in: Second Language Research DOI: 10.1177/0267658315573349…”
Section: Importance For Text Processing and Comprehensionmentioning
confidence: 99%
“…Numerous studies have demonstrated the positive impact of cohesion devices on the memory of causally connected sentences compared to isolated sentences (Trabasso and van den Broek, 1985; cf. Myers et al, 1987; Fletcher and Bloom, 1988) and on reading comprehension (Degand et al, 1999; Linderholm et al, 2000; Degand and Sanders, 2002; Maury and Teisserenc, 2005; Sanders et al, 2007; Van Silfhout et al, 2014a,b, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While reading in their first language, readers directly benefit from connectives since they increase the local and global comprehension of a text (e.g., Degand et al 1999;Van Silfhout et al 2014), increase processing speed (Murray 1997;Sanders and Noordman 2000) and improve recall of its content (Caron et al 1988). However, learners even at an advanced stage of language acquisition still lag behind native speakers in their mastery of connectives in L2.…”
Section: Introductionmentioning
confidence: 99%